The Association Between Dietary Inflammatory Index and Sex Hormones Among Postmenopausal Women in the US - Chen, Wen-Yu; Fu, Yan-Peng; Zhong, Wen; Zhou, Min (Frontiers in Endocrinology, 2021)
Aims Diet has been found to have an important effect on sex hormones. The effect of diet-induced inflammation on sex hormones has not been studied in detail among women. Therefore, we aimed to investigate the association between energy-adjusted dietary inflammatory index (E-DII) and sex hormones among postmenopausal women. Methods This study used data from the National Health and Nutrition Examination Survey (NHANES) 2013–2016 waves. A total of 1183 postmenopausal women who provided information on two 24-hour dietary intake recalls, sex hormones including total testosterone (TT), estradiol (E2), TT/E2, sex hormone-binding globulin (SHBG), free estradiol (FE2) and free testosterone (FT), as well as selected covariates were included. Linear regression and restricted cubic spline evaluated the association between E-DII and sex hormones. Effect modification by body mass index (BMI) and type of menopause was then examined in stratified analysis. Results After adjusting for covariates, linear regression showed that E-DII was positively associated with TT (P=0.035), FT (P=0.026) and TT/E2 (P=0.065). TT (P-nonlinear = 0.037) and TT/E2 (P-nonlinear = 0.035) had significant nonlinear association with E-DII. E2 (P-nonlinear = 0.046) and FE2 (P-nonlinear = 0.027) depicted a nonlinear U-shaped significant association with E-DII, the two inflection points were found at the E-DII score of -0.22 and 0.07, respectively, the associations in natural menopausal women were more pronounced. Conclusions Our study indicates that several indicators of androgen and estrogen were associated with E-DII in postmenopausal women. Further research is needed to understand the underlying mechanisms.